PARALLEL IMPORTS AS A SPHERE OF CONFLICT BETWEEN THE INTERESTS OF CONSUMERS AND RIGHT HOLDERS - Lobanova Galina Yurievna (Modern American Journals, 2026)
Parallel imports refer to the circulation of original (non-counterfeit) goods outside official distribution channels. The legal sensitivity of this phenomenon is associated with the doctrine of exhaustion of trademark rights: after a product has been lawfully placed on the market, the right holder, to a certain extent, loses the ability to control the дальнейшее distribution of a particular copy of the goods. The article analyses the current legal regulation of parallel imports in the Republic of Uzbekistan, as well as international approaches to this issue, including the provisions of the TRIPS Agreement and the materials of the World Intellectual Property Organization (WIPO).
Keywords: Parallel imports, exhaustion of rights, trademark, competition, consumer protection, abuse of rights, Republic of Uzbekistan, TRIPS.